The Influence of Product Quality and Price Perception on the Purchase Decision of Emina Products at Scovia Store in Pontianak - Maria Gonela; Samsuddin Samsuddin (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of product quality and price perception on the purchase decision of Emina products at Scovia Store in Pontianak, in response to the decline in sales from 2022 to 2024. Using a quantitative associative approach, the research involved 100 respondents selected through purposive sampling, with criteria including consumers aged at least 17 years and having purchased Emina products more than once. Primary data were obtained through interviews and structured questionnaires, while secondary data were sourced from internal documents related to product types, prices, and sales records. Instrument testing showed that all questionnaire items met validity and reliability requirements. The data were analyzed using multiple linear regression, supported by classical assumption tests. The results indicate that both product quality and price perception have a positive and significant influence on purchase decisions, with product quality contributing the strongest effect. The regression model explains 48.5% of the variance in purchase decisions, while the remaining 51.5% is influenced by other factors outside this study. These findings highlight the importance of maintaining product quality and aligning pricing strategies with consumer value perceptions to strengthen consumer purchasing decisions. The study provides practical insights for retail management and contributes empirically to consumer behavior literature, particularly in the cosmetics industry. Future research may extend the model by incorporating variables such as brand image, promotion, or service quality to obtain a more comprehensive explanation of consumer decision-making.